The entirety of memory and its otherness. Phenomenological approach - Jonkus, Dalius (Religija ir kultūra, 2009)
The aim of this article is to demonstrate that memory is not identical with full consciousness. Memory is related to forgetting, but memory cannot be reduced to it. The errors and illusions of memory do not negate it because they can be discovered only within the context of the entirety of memory. On this account I agree with Paul Ricoeur, who warns against the inadmissible reduction of memory to memory pathologies. When Husserl analyses the problem of memory, he has to overcome the traditional distrust in memory, to show that memory is not a form of image consciousness, and to create a dynamic model of memory. First, I will show how the static understanding of memory as a set of copies works. Second, I will analyse how the concept of memory changes when it is correlated with reproductive presentification. Third, I will elaborate on how it is possible to identify false memories. Fourth, I will analyse how passive synthesis of associations manifests itself in memories. And fifth, I will demonstrate how memory is related to forgetting.